An iso-α-acid-rich extract from hops (Humulus lupulus) attenuates acute alcohol-induced liver steatosis in mice - Hege, Marianne; Jung, Finn; Sellmann, Cathrin; Jin, Chengjun; Ziegenhardt, Doreen; Hellerbrand, Claus; Bergheim, Ina (Nutrition, 2018)
OBJECTIVE: Results of in vitro and in vivo studies suggest that consumption of beer is less harmful for the liver than consumption of spirits. It also has been suggested that secondary plant compounds derived from hops such as xanthohumol or iso-α-acids may have beneficial effects on the development of liver diseases of various etiologies. The aim of this study was to determine whether iso-α-acids consumed in doses achieved by "normal" beer consumption have beneficial effects on health. METHODS: Female C57 Bl/6 J mice, pretreated for 4 d with an iso-α-acid-rich extract (∼30% iso-α-acids from hops, 0.75 mg/kg body weight), were fed one bolus of ethanol (6 g/kg body weight intragastric) or an iso-caloric maltodextrin solution. Markers of liver damage, toll-like receptor-4 signaling, and lipid peroxidation were determined. Furthermore, the effect of isohumulone on the lipopolysaccharide-dependent activation of J774 A.1 macrophages, used as a model of Kupffer cells, was determined. RESULTS: In the liver, acute ethanol administration led to a significant accumulation of fat (∼10-fold), which was accompanied by significantly higher inducible nitric oxide synthase protein level, elevated nitric oxide production, and increased plasminogen activator inhibitor 1 protein concentration when compared to controls. In mice pretreated with iso-α-acids, these effects of alcohol were markedly attenuated. Pretreatment of J774 A.1 macrophages with isohumulone significantly attenuated lipopolysaccharide-induced mRNA expression of inducible nitric oxide synthase and interleukin-6 as well as the release of nitric oxide. CONCLUSION: Taken together, iso-α-acids markedly attenuated the development of acute alcohol-induced damage in mice.
EVALuna2:35802